Speed from light: growth rate and bulk flow at z ∼ 0.1 from improved SDSS DR13 photometry. Issue 2 (4th March 2017) - Feix, M.; Branchini, E.; Nusser, A.
Abstract: Observed galaxy luminosities (derived from redshifts) hold information on the large-scale peculiar velocity field in the form of spatially correlated scatter, which allows for bounds on bulk flows and the growth rate of matter density perturbations using large galaxy redshift surveys. We apply this luminosity approach to galaxies from the recent SDSS Data Release 13. Our goal is twofold. First, we take advantage of the recalibrated photometry to identify possible systematic errors relevant to our previous analysis of earlier data. Second, we seek improved constraints on the bulk flow and the normalized growth rate f σ8 at z ∼ 0.1. Our results confirm the robustness of our method. Bulk flow amplitudes, estimated in two redshift bins with 0.02 < z 1 < 0.07 < z 2 < 0.22, are generally smaller than in previous measurements, consistent with both the updated photometry and expectations for the Λ cold dark matter model. The obtained growth rate, f σ8 = 0.48 ± 0.16, is larger than, but still compatible with, its previous estimate, and closer to the reference value of Planck. Rather than precision, the importance of these results is due to the fact that they follow from an independent method that relies on accurate photometry, which is a top requirement for next-generation photometric catalogues.